2017
DOI: 10.1002/asmb.2272
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the multivariate dispersion charts with estimated parameters under non‐normality

Abstract: Various charts such as |S|, W, and G are used for monitoring process dispersion. Most of these charts are based on the normality assumption, while exact distribution of the control statistic is unknown, and thus limiting distribution of control statistic is employed which is applicable for large sample sizes. In practice, the normality assumption of distribution might be violated, while it is not always possible to collect large sample size. Furthermore, to use control charts in practice, the in‐control state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Besides that, in general, estimation to the in-control state of the control charts has to be carried out, but this will have adverse impact on the performance of the control chart. As indicated in Mostajeran et al in [7], non-parametric bootstrap control charts are appropriate for an unidentified distribution or when making estimation on the process parameters from Phase I dataset or when it is impractical to gather sample of large size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, in general, estimation to the in-control state of the control charts has to be carried out, but this will have adverse impact on the performance of the control chart. As indicated in Mostajeran et al in [7], non-parametric bootstrap control charts are appropriate for an unidentified distribution or when making estimation on the process parameters from Phase I dataset or when it is impractical to gather sample of large size.…”
Section: Introductionmentioning
confidence: 99%
“…In Mostajeran et al [7], the authors presented the use of non-parametric bootstrap multivariate control charts |S|, W, and G, and this method is grounded upon the use of bootstrapped data in the estimation of the in-control state. In this study, the authors succeeded in obtaining satisfactory performance of bootstrap [12] demonstrated the application of a bootstrap multivariate control chart and compared it with a Hotelling's T 2 parametric multivariate control chart, a multivariate sign control chart, and a multivariate Wilcoxon control chart.…”
Section: Introductionmentioning
confidence: 99%